2001
DOI: 10.1186/1297-9686-33-6-587
|View full text |Cite
|
Sign up to set email alerts
|

A sampling algorithm for segregation analysis

Abstract: -Methods for detecting Quantitative Trait Loci (QTL) without markers have generally used iterative peeling algorithms for determining genotype probabilities. These algorithms have considerable shortcomings in complex pedigrees. A Monte Carlo Markov chain (MCMC) method which samples the pedigree of the whole population jointly is described. Simultaneous sampling of the pedigree was achieved by sampling descent graphs using the MetropolisHastings algorithm. A descent graph describes the inheritance state of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For example, the FPM part of the TR* models explained a significant fraction of the genetic variance in the S50 and S50s simulation scenarios, although no major genes were simulated, a result that was also reported by Tier & Henshall (2001). In these cases, one should base inferences on the full posterior density of the genetic variance (or heritability) of the FPM instead of only the posterior mean.…”
Section: (Iii) Mixed Inheritance Modelsmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, the FPM part of the TR* models explained a significant fraction of the genetic variance in the S50 and S50s simulation scenarios, although no major genes were simulated, a result that was also reported by Tier & Henshall (2001). In these cases, one should base inferences on the full posterior density of the genetic variance (or heritability) of the FPM instead of only the posterior mean.…”
Section: (Iii) Mixed Inheritance Modelsmentioning
confidence: 88%
“…In the computation of probabilities of gene descent in pedigrees, these meiosis indicators have also been called inheritance vectors (Lander & Green, 1987), descent graphs (Sobel & Lange, 1996) and segregation indicators (Thompson, 1994). Implementation of descent graphs to sample genotypes jointly for all individuals has been explored by Tier & Henshall (2001) and Du & Hoeschele (2000) ; Du and Hoeschele reported that the joint sampling procedure did not improve the parameter estimation compared with simpler implementation of descent graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Computationally, a descent graph can be stored and manipulated most efficiently using bit representation, with one 32-bit integer word encoding the meiosis indicators of 16 individuals, as suggested by Tier and Henshall (2001). For single (Tier and Henshall, 2001) or multiple unlinked loci (Du and Hoeschele, 2000a) with no genotype information available, genotype sampling can be performed by proposing small changes to the founder alleles and/or the descent graph in each cycle, and accepting or rejecting these in an MH step. Changes to the founder alleles are proposed by resampling a few alleles according to allele frequencies, and changes to the descent graph are proposed by swapping a few inheritance states.…”
Section: )mentioning
confidence: 99%
“…(1993) describe a non‐iterative, recursive method to compute the likelihood for a pedigree without loops. ‘The Gene Detective’ ( Tier and Henshall 2001) is a software based on MCMC (Markov Chain Monte Carlo) methods that sample the whole pedigree jointly. Maximum likelihood methods combined with iterative peeling, in which information from progressively more distant relatives is used with each further iterate, is the basis for the method of segregation analysis used in this study ( Kerr and Kinghorn 1996).…”
Section: Introductionmentioning
confidence: 99%